The Effects of Endowment, Mental Accounting, and Illusion of Control Biases on Liberal Accounting - Eko Widodo Lo (International Journal of Advanced Science and Technology, 2020)
This research examines the influences of endowment, mental accounting, and control illusion biases on liberal accounting. This study collects data by a survey method. The validity and reliability of instruments are tested by factor analysis and Cronbach’s alpha. The research sample consists of senior accounting students at a business school in Yogyakarta, Indonesia. Hypotheses of research are examined by multiple regression analysis. Results of empirical data analysis indicate that endowment and control illusion biases positively affect liberal accounting. This study provides two contributions. First, this attempts to relate endowment, mental accounting, and control illusion biases on liberal accounting decisions. This contributes to an additional explanation of accounting decision making among accountants. Second, the conclusions of this research can be utilized to specify the proper psychological characteristics among accountants for certain accounting policies.